Pradosia Liais (Sapotaceae) do Nordeste: uma abordagem micromorfológica - Almeida, Elisama da Silva (2019)
The Brazilian Northeast comprises a huge vegetation variation composed of several groups, among which is the family Sapotaceae, that has a well established economic and ecological importance. The present study aimed to analyze, through techniques of plant micromorphology and histochemistry, the leaves of the species of Pradosia Liais cited for the region, aiming to contribute with information to its internal structure, to indicate the present metabolites as well as expanding data on gender and family. The leaf surface was analyzed by light microscopy and scanning electron microscopy. For the analysis of the internal structure and metabolites, cross sections of the petiole and leaf blade were performed freehand and with freezing microtome following the usual literature of the plant micromorphology. The analysis of the leaf surface, performed for the first chapter, offers data to distinguish the species and denotes some adaptations to extreme environments such as cuticular ornamentation, the position of the stomata on the leaves and presence of inclusions in the epidermal cells. The second chapter indicates that the contour of the petiole and the arrangement of the vascular cylinder and the midrib are the main diagnostic characters for the delimitation of the studied species and point to subepidermal layers and girders in the mesophyll as main adaptive characters. Histochemical analysis points to the need for more accurate studies including, also, other organs. It should be emphasized that the present work provided unpublished data that will serve as a subsidy for later studies.